The return of industrial policies Policy considerations in the current context - Millot, Valentine (OECD Economic Policy Papers, 2023)
The paper contributes to renewed debates about industrial policy in the context of recent initiatives in several OECD economies. It discusses the pros and cons of industrial policies motivated by environmental, national security and place-based/inclusiveness objectives. The paper also considers implementation and design issues, and how to respond to industrial policies in foreign countries. Despite well-grounded economic, social and environmental justifications for some industrial policies, there are legitimate concerns that the benefits of some of these policies could be limited and the costs high. This mainly relates to measures curbing competition and the practical and political challenges in designing and implementing effective measures. Thus, while governments may want to experiment with future and welfare-oriented industrial policies, they should exert moderation in scope, exercise caution in design and implementation, and be mindful of possible negative international implications